2008
DOI: 10.1002/chem.200701870
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NH2 Functionality and Solvent in Terdentate CNN Alkoxide Ruthenium Complexes for the Fast Transfer Hydrogenation of Ketones in 2‐Propanol

Abstract: The reaction of [RuCl(CNN)(dppb)] (1; HCNN=6-(4-methylphenyl)-2-pyridylmethylamine) with NaOiPr in 2-propanol/C6D6 affords the alcohol adduct alkoxide [Ru(OiPr)(CNN)(dppb)].n iPrOH (5), containing the Ru-NH2 linkage. The alkoxide [Ru(OiPr)(CNN)(dppb)] (4) is formed by treatment of the hydride [Ru(H)(CNN)(dppb)] (2) with acetone in C6D6. Complex 5 in 2-propanol/C6D6 equilibrates quickly with hydride 2 and acetone with an exchange rate of (5.4+/-0.2) s(-1) at 25 degrees C, higher than that found between 4 and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 62 publications
4
48
0
Order By: Relevance
“…We found that the reaction of 36a with sodium isopropoxide in 2-propanol/C 6 D 6 afforded the alcohol-adduct alkoxide 60, which is in equilibrium with the hydride 38a/acetone mixture (Scheme 73) [52]. The hydride 38a was isolated from 36a and NaOiPr in 2-propanol/toluene by evaporation of the alcohol media and elimination of acetone under reduced pressure [32].…”
Section: Mechanistic Studies On Hydrogen Transfer and Hydrogenation Mmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that the reaction of 36a with sodium isopropoxide in 2-propanol/C 6 D 6 afforded the alcohol-adduct alkoxide 60, which is in equilibrium with the hydride 38a/acetone mixture (Scheme 73) [52]. The hydride 38a was isolated from 36a and NaOiPr in 2-propanol/toluene by evaporation of the alcohol media and elimination of acetone under reduced pressure [32].…”
Section: Mechanistic Studies On Hydrogen Transfer and Hydrogenation Mmentioning
confidence: 99%
“…Moreover, 31 P-31 P NMR NOESY in solution revealed a rapid equilibrium between the alkoxide 37a and 38a/acetone mixture with an exchange rate of 2.9 ± 0.4 s −1 . Interestingly, the alkoxide 60 containing 2-propanol equilibrates with the hydride 38a with a significant higher rate (5.4 ± 0.2 s −1 ), showing that alcohol has a crucial role in enhancing the rate of exchange process [52]. Substitution in 36a of the NH 2 group with the NMe 2 function 36b produced a poorly active TH catalyst [32b].…”
Section: Mechanistic Studies On Hydrogen Transfer and Hydrogenation Mmentioning
confidence: 99%
See 3 more Smart Citations